Behavior of Ricinus communis L. plants due to different volumes of containers and substrates - Andrade, Francisco Hélio Alves de; Araújo, Carla Sabrina Pereira de; Clemente, Maria Isabela Batista; Silva, Josevan de Andrade; Morais, Rafael Ramos de; Sousa, Valéria Fernandes de Oliveira (Acta Iguazu, 2018)
Abstract: The objective of this study was to evaluate the production of castor bean seedlings due to different volumes of containers and substrates. The work was conducted from May to June 2014, in the nursery of the State University of Paraíba, Campus IV, Catolé do Rocha, PB. The experimental design was a completely randomized design, adopting the 4 x 2 factorial scheme, with 6 replicates, with four container volumes: (polyethylene plastic bags with capacity 1000 dm³; polyethylene plastic bags with a capacity of 500 dm³; tubes with a capacity of 300 dm³ and disposable cups with a capacity of 270 dm³) and two types of substrates (S1 = 50% soil + 50% earthworm humus and S2 = 40% soil + 30% earthworm humus + 30% sand). The variables studied were: (LN) leaf number; (ULA) unitary leaf area; (RD) root diameter; (RL) root length; (SB) shoot biomass; (TPB) total plant biomass. All variables had a significant effect on cantainer volumes. Probably the largest container provided larger area of substrate to be explored. Castor bean seedlings of the BRS Gabriela variety respond well to larger container volumes. The substrate V1 (50% soil and 50% humus) influenced the initial growth of BRS Gabriela seedlings.